2015
DOI: 10.1093/schbul/sbv125
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Comparison of Aripiprazole and Risperidone for the Acute Treatment of First-Episode Schizophrenia and Related Disorders: 3-Month Outcomes

Abstract: Research findings are particularly important for medication choice for first-episode patients as individual prior medication response to guide treatment decisions is unavailable. We describe the first large-scale double-masked randomized comparison with first-episode patients of aripiprazole and risperidone, 2 commonly used first-episode treatment agents. One hundred ninety-eight participants aged 15-40 years with schizophrenia, schizophreniform disorder, schizoaffective disorder or psychotic disorder Not Othe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
78
1
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 105 publications
(90 citation statements)
references
References 27 publications
9
78
1
2
Order By: Relevance
“…Among the atypical antipsychotics, aripiprazole is known to be prolactin-sparing, whereas others, including risperidone, are considered to be prolactin-raising. 42,48 The present study did not reveal any clinically meaningful alterations in prolactin levels with AOM 400 versus placebo, and there were few TEAEs related to prolactin or sexual dysfunction.…”
Section: Discussionmentioning
confidence: 44%
“…Among the atypical antipsychotics, aripiprazole is known to be prolactin-sparing, whereas others, including risperidone, are considered to be prolactin-raising. 42,48 The present study did not reveal any clinically meaningful alterations in prolactin levels with AOM 400 versus placebo, and there were few TEAEs related to prolactin or sexual dysfunction.…”
Section: Discussionmentioning
confidence: 44%
“…Extrapyramidal syndrome is a commonly observed side effect, especially for the first generation antipsychotics, such as haloperidol, which generally require high striatal D 2 receptor occupancy for efficacy and consequently result in motor disturbances such as parkinsonism and akathisia [174, 190]. It has been suggested for first-episode patients that aripiprazole may be considered as the preferred choice over risperidone; however, if the potential for akathisia and poor impulse control is a concern, low-dose risperidone may be a better choice over aripiprazole [191]. Clozapine demonstrated less severe motoric side effects, which is likely due to the relatively lower D 2 receptor occupancy at therapeutic doses [194].…”
Section: Comparison Of Representative Antipsychotics Haloperidol CLmentioning
confidence: 99%
“…This higher discontinuation rate seems to be related not only to extrapyramidal symptoms but also to some other disadvantages of FGAs, as they may produce more secondary negative and cognitive symptoms [32]. Additionally, these negative effects do not seem to be homogeneous among different medications within the SGA group [33, 34]. …”
Section: Aiming For Efficacy and Effectivenessmentioning
confidence: 99%
“…Most of the medium-term randomized studies have shown similar rates of clinical response and all-cause treatment discontinuation in people with a FEP treated with other SGAs (risperidone, olanzapine, ziprasidone, aripiprazole, amisulpride) [28, 31]. Robinson et al [33] showed a similar efficacy and effectiveness between aripiprazole and risperidone for the acute treatment of first-episode schizophrenia. Olanzapine might lead to longer treatment maintenance than haloperidol or ziprasidone in treatment-naïve people with a FEP [40].…”
Section: Aiming For Efficacy and Effectivenessmentioning
confidence: 99%